2015
DOI: 10.3762/bjoc.11.163
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a tricyclic lactam via Beckmann rearrangement and ring-rearrangement metathesis as key steps

Abstract: SummaryA tricyclic lactam is reported in a four step synthesis sequence via Beckmann rearrangement and ring-rearrangement metathesis as key steps. Here, we used a simple starting material such as dicyclopentadiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Assuming that the Lewis acid coordinated to either hydroxy oxygen atom or to one of the oxygen atoms of the mesyl group, the activation energies for C-O bond dissociation are ca. All of these experiments suggested that the transformation of β-hydroxyalkylphosphine sulfides in the presence of Lewis acid most probably proceeded through the initial formation of an intermediate alkenylphosphine sulfide, which then underwent an intramolecular reaction leading to a formal [1,4]-rearrangement product. It seemed that the position of the double bond was crucial for the rearrangement, which had to be situated between the β-and the γ-carbon atom.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Assuming that the Lewis acid coordinated to either hydroxy oxygen atom or to one of the oxygen atoms of the mesyl group, the activation energies for C-O bond dissociation are ca. All of these experiments suggested that the transformation of β-hydroxyalkylphosphine sulfides in the presence of Lewis acid most probably proceeded through the initial formation of an intermediate alkenylphosphine sulfide, which then underwent an intramolecular reaction leading to a formal [1,4]-rearrangement product. It seemed that the position of the double bond was crucial for the rearrangement, which had to be situated between the β-and the γ-carbon atom.…”
Section: Methodsmentioning
confidence: 99%
“…The rearrangement in the presence of Brønsted-acidic H 2 SO 4 afforded only minor amounts of S-acylated γ-mercaptoalkylphosphine oxide 68, but the enantiomeric excess was even higher than in the substrate. This suggested that the [1,3]-rearrangement was stereospecific in the presence of Brønsted acid, whereas the [1,4]-rearrangement proceeded with additional partial enrichment of one enantiomer. The latter may have occurred through the preferential acylation of one of two diastereoisomers under the reaction conditions where the second chirality center at the phosphorus atom influenced the ratio of the acylation reaction.…”
Section: Scheme 11mentioning
confidence: 99%
See 3 more Smart Citations